Optimizing carbon nanotube-doped ternary composite for high-energy-density hybrid supercapacitors: A comprehensive electrochemical assessment through central composite design - Verma S.; Verma B. (My University, 2025)
In today's cutting-edge scientific world, the interest in renewable energy sources is continuously increasing. To construct a cost-effective system with enhanced energy efficiency, endeavors have been heightened to innovate renewable energy storage systems. Designing materials with new electrodes that have controlled structure and composition is tedious. In recent years, hybrid supercapacitors have been developed with increased energy density efficiency without affecting power density efficiency. Here, graphene oxide, carbon nanotubes, and copper cobaltite have been combined to form the ternary composite material known as GO/CNT/CC using a chemical process. The varying GO and CC weight % effect on electrochemical nature is optimized using response surface methodology's (RSM) central composite design (CCD) approach. The optimized weight % ternary electrode had a maximum 635.97 F/g specific capacitance at 1 mV/s using the 3E system which is much higher than binary GO/CNT (382.61 F/g) and GO (154.48 F/g). In addition, optimize ternary GO/CNT/CC also has 87.69 % retention after 8000 cycles with 41.95 Wh/kg of specific energy. The synergistic interaction between GO and CNT in ternary hybrids enables electrolyte ions admittance to the active material electrode during the electrochemical reaction and maintains the mechanical strength and is responsible for these improvements. © 2024 The Korean Society of Industrial and Engineering Chemistry